Zinc supplementation alleviates heat stress in laying Japanese quail - Şahin, Kazım; Küçük, Ömer (Amer Inst Nutrition, 2003)
The study was conducted to determine whether zinc supplementation could alleviate the detrimental effects of high ambient temperature (34degreesC) on egg production, digestibility of nutrients and antioxidant status in laying Japanese quail. Quail (n = 180; 52 d old) were divided into six groups (n = 30/group) and were fed a basal diet or the basal diet supplemented with 30 or 60 mg of zinc (ZnSO4 (.) H2O)/kg diet. Birds were kept at 22degreesC and 58% relative humidity (RH). At 13 wk of age, the thermoneutral [TN) groups remained at the same temperature, whereas the heat-stress (HS) groups were kept in an environmentally controlled room at 34degreesC and 42% RH for 3 wk. Heat exposure decreased egg production in birds fed the basal diet (P = 0.001). Linear increases in feed intake (P = 0.01) and egg production (P = 0.0004) and improved feed efficiency (P = 0.01) and egg quality variables (Pless than or equal to 0.05) occurred in zinc-supplemented groups reared under HS conditions. Heat exposure decreased digestibility of nutrients (P = 0.001), and these decreases were ameliorated by zinc supplementation (P less than or equal to 0.05). Serum vitamin C (P = 0.05), vitamin E (P = 0.01) and zinc (P = 0.001) concentrations increased linearly, whereas malondialdehyde concentrations decreased (P = 0.002) as dietary zinc supplementation increased. No significant differences in any values were observed in the TN groups (P > 0.05). Results of the present study suggest that supplementation with 60 mg zinc/kg diet protects quail by reducing the negative effects of heat stress.
Keywords: zinc; egg; antioxidant status; heat stress; quail